Psychometric properties of the intensive care delirium screening checklist when used by bedside nurses in clinical practice: a prospective descriptive study - Elke Detroyer; Annick Timmermans; Dana Segers; Geert Meyfroidt; Jasperina Dubois; Aimé Van Assche; Etienne Joosten; Koen Milisen (BMC, 2020)
Abstract Background The Intensive Care Delirium Screening Checklist (ICDSC) demonstrates good psychometric characteristics in research settings. However, evidence about these characteristics in pragmatic ICU settings is inconsistent. This study evaluated psychometric properties and user-friendliness of the ICDSC when administered by ICU nurses in daily practice. Methods This prospective study included 77 patients from a surgical intensive care unit. To examine the psychometric characteristics, the scores on the ICDSC (performed by bedside nurses) were compared with the scores on the Confusion Assessment Method for the Intensive Care Unit (CAM-ICU) (performed by researchers as gold standard). The user-friendliness was evaluated by 34 ICU nurses with a 20-item questionnaire. Results The ICDSC had an area under the curve of 0.843. It showed a good diagnostic accuracy with a sensitivity of 81.0%, a specificity of 87.7%, and a 53.1% positive and 96.4% negative predictive value. The overall Cronbach's alpha coefficient for all ICDSC scores was high (0.839). Overall, ICU nurses experienced the ICDSC as easy-to-use. The scale was usable in most surgical ICU patients. Yet, some nurses (11.8%) had problems to score the items 'inappropriate speech' and 'symptom fluctuation' in intubated patients. Conclusions The ICDSC is a valid and user-friendly tool for delirium screening in daily ICU nursing practice. Yet, some problems were reported in intubated patients. Therefore, validation studies with specific focus on intubated patients are needed.